Capital Accumulation and Foreign Investment Taxation - Sibert, Anne C. (Review of Economic Studies, 1985)
This paper presents a dynamic, choice-theoretic general equilibrium model of capital accumulation in an open economy. Equilibria with and without capital mobility are described and compared. It is shown that neither is necessarily Pareto optimal and that an equilibrium with free trade in capital does not Pareto-dominate an equilibrium with autarky. The effects of restricting capital flows by taxing foreign investment earnings are discussed. It is seen that there will be no agreement within a country as to what constitutes an optimal tax. 1.